Impact of maternal depressive symptoms and infant temperament on early infant growth and motor development: results from a population based study in Bangladesh - Nasreen, Hashima-E; Kabir, Zarina Nahar; Forsell, Yvonne; Edhborg, Maigun (© 2013 Journal of Affective Disorders, 2017)
This article was published in the Journal of Affective Disorders [© 2012 Elsevier B.V.] and the definite version is available at: http://europepmc.org/abstract/med/23063237